Arabisation, globalisation, and Hebraisation reflexes in shop names in the Palestinian Arab linguistic landscape in Israel. (4th May 2019) - Amara, Muhammad
ABSTRACT: Proper names are widely found in the linguistic landscape including shop names. They transmit factual information and are used to appeal to emotions representing 'symbolic rather than structural or semantic expression'. The current study investigates shop names in six Palestinian Arab localities in Israel employing quantitative and qualitative research methods. Photographs of 848 shop names from the six Palestinian Arab localities facilitated examining the type of names, scripts used, and the type of business. Six shop owners were interviewed about their shop names, types, and scripts. The findings reveal that Arabic is the most prominent language used, followed by foreign languages, with Hebrew far behind. Locality and type of business are found to be important factors, revealing that Palestinian Arab shop names are not homogeneous and certain languages are preferred in some businesses rather than others. Palestinian Arabs work on maintaining their Palestinian-Arab identity in the conflict-ridden Israeli reality. Besides, they are also influenced by Hebraisation through the exposure to Israeli culture and its values, as well as to globalization, which entails being connected with worldwide trends.